Respuesta :

Answer:

x = -5.6 ±sqrt(1.75)

x≈-4.28                        x≈-6.92

Step-by-step explanation:

(x + 5.6)^2 = 1.75

Take the square root of each side

sqrt((x + 5.6)^2) = ±sqrt(1.75)

x+5.6 = ±sqrt(1.75)

Subtract 5.6 from each side

x+5.6 -5.6 = -5.6 ±sqrt(1.75)

x = -5.6 ±sqrt(1.75)

x= -5.6 + sqrt(1.75)       x = -5.6 - sqrt(1.75)

x≈-4.27712                   x≈-6.92288

x≈-4.28                        x≈-6.92

Answer:

x = sqrt(1.75) - 5.6, -sqrt(1.75) - 5.6,

x ≈ -4.28, -6.92

Step-by-step explanation:

(x + 5.6)² = 1.75

(x + 5.6) = +/- sqrt(1.75)

x = +/- sqrt(1.75) - 5.6

x ≈ -4.28, -6.92